Pengembangan Sistem Pengelolaan Aset Fakultas Ilmu Komputer Universitas Brawijaya - Anggi Wiyani Putri Nasution; Tri Astoto Kurniawan; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
FILKOM has total assets of 15,416 items in 2018 within FILKOM. Asset management has several activities such as proposal for procurement of goods, procurement of goods, receipt of goods and movement of goods. Asset management carried out by FILKOM often has incosistency in its records so that the goods are often not found or goods are found but the information is not known. In addition, the problem of asset management activities that do not follow the terms of the Standard Operational Procedure (SOP) in the activity movement of goods the probability of finding lost items is getting lower. In addition, lecturers and staff who have the authority to apply for procurement of goods cannot even know that their request has been approved or rejected if they do not enquire. Not only that, information regarding the procurement of goods and receipt of goods is also not known clearly or transparently. A web-based Asset Management System was developed to solve these issues. The development of this system using the Waterfall model with an object-oriented approach. This system has been tested using unit testing, integration and validation. Unit and integration testing using whitebox testing and validation testing using blackbox testing. The results of the test get 100% valid for all the tests.